TRK Inhibitors: Tissue-Agnostic Anti-Cancer Drugs - Han, Sun-Young (Pharmaceuticals (Basel), 2021)
Recently, two tropomycin receptor kinase (Trk) inhibitors, larotrectinib and entrectinib, have been approved for Trk fusion-positive cancer patients. Clinical trials for larotrectinib and entrectinib were performed with patients selected based on the presence of Trk fusion, regardless of cancer type. This unique approach, called tissue-agnostic development, expedited the process of Trk inhibitor development. In the present review, the development processes of larotrectinib and entrectinib have been described, along with discussion on other Trk inhibitors currently in clinical trials. The on-target effects of Trk inhibitors in Trk signaling exhibit adverse effects on the central nervous system, such as withdrawal pain, weight gain, and dizziness. A next generation sequencing-based method has been approved for companion diagnostics of larotrectinib, which can detect various types of Trk fusions in tumor samples. With the adoption of the tissue-agnostic approach, the development of Trk inhibitors has been accelerated.